2010
DOI: 10.1101/gr.103622.109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of translocation-induced nuclear reorganization on gene expression

Abstract: Translocations are known to affect the expression of genes at the breakpoints and, in the case of unbalanced translocations, alter the gene copy number. However, a comprehensive understanding of the functional impact of this class of variation is lacking. Here, we have studied the effect of balanced chromosomal rearrangements on gene expression by comparing the transcriptomes of cell lines from controls and individuals with the t(11;22)(q23;q11) translocation. The number of differentially expressed transcripts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 72 publications
4
77
0
1
Order By: Relevance
“…(Merla et al 2006;Guryev et al 2008;Cahan et al 2009;Henrichsen et al 2009b). Interestingly, recent results have shown that structural variants can have an effect on normal copy number genes positioned along the entire length of a chromosome (Harewood et al 2010;Ricard et al 2010). Our analyses also corroborate the finding that genes within CNVs have particular properties with respect to their spatial expression patterns and dosage sensitivity (Henrichsen et al 2009b).…”
Section: à7supporting
confidence: 87%
“…(Merla et al 2006;Guryev et al 2008;Cahan et al 2009;Henrichsen et al 2009b). Interestingly, recent results have shown that structural variants can have an effect on normal copy number genes positioned along the entire length of a chromosome (Harewood et al 2010;Ricard et al 2010). Our analyses also corroborate the finding that genes within CNVs have particular properties with respect to their spatial expression patterns and dosage sensitivity (Henrichsen et al 2009b).…”
Section: à7supporting
confidence: 87%
“…Recent observations indicate that the radial distribution of CTs affects the expression of a number of genes, but does not necessarily correlate with gene expression (Harewood et al, 2010;Küpper et al, 2007;Meaburn and Misteli, 2008). Similar results were obtained in 'tethering' experiments (Kumaran and Spector, 2008;Reddy et al, 2008).…”
Section: Transcriptional Misregulation In Arp6-and H2az-deficient Cellssupporting
confidence: 53%
“…"copy-neutral" structural variants) can affect gene expression as well, either by changing regulatory elements or creating positional effects (Harewood et al, 2010(Harewood et al, , 2012Haraksingh and Snyder, 2013). Homologous genes involved in structural variations between the genomes of S. parvula and Arabidopsis contained more divergent promoters (Fig.…”
Section: Genome Structure Shapes the Transcriptomementioning
confidence: 99%